2020
DOI: 10.1002/jum.15466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Common Carotid Stiffness via Echo Tracking in Hypertensive Patients Complicated by Acute Aortic Dissection

Abstract: Objectives To evaluate the common carotid stiffness via echo tracking in patients with hypertension and acute aortic dissection (AD) and to investigate the independent predictors for the occurrence of AD in hypertensive (HP) patients. Methods Fifty HP patients complicated by acute AD (AD group), 50 HP patients without AD (HP group), and 50 age‐matched healthy volunteers (control group) were enrolled to assess the common carotid stiffness index (β), single‐point pulsed wave velocity (PWVβ), and arterial complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Given the significant mortality and poor prognosis, it is crucial to find some additional parameters to identify the hypertensive (HP) individuals at high risk of AAD. Our previous study has confirmed that the biomechanical parameters such as carotid arterial stiffness could be a supplemental indicator to predict AAD 6 . Hence, we deduced that the quantitative evaluation of ascending aortic mechanical behaviors might be another potentially personalized risk parameter in HP patients.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Given the significant mortality and poor prognosis, it is crucial to find some additional parameters to identify the hypertensive (HP) individuals at high risk of AAD. Our previous study has confirmed that the biomechanical parameters such as carotid arterial stiffness could be a supplemental indicator to predict AAD 6 . Hence, we deduced that the quantitative evaluation of ascending aortic mechanical behaviors might be another potentially personalized risk parameter in HP patients.…”
supporting
confidence: 58%
“…Our previous study has confirmed that the biomechanical parameters such as carotid arterial stiffness could be a supplemental indicator to predict AAD. 6 Hence, we deduced that the quantitative evaluation of ascending aortic mechanical behaviors might be another potentially personalized risk parameter in HP patients.…”
mentioning
confidence: 98%
“…Gu et al [14] evaluated the carotid stiffness of 150 researchers (including 50 hypertensive patients, 50 patients with acute aortic dissection and 50 healthy people) by ET. The results showed that the stiffness values (β and PWVβ) of the common carotid artery (CCA) in the acute aortic dissection group were significantly higher than those in the control group, and the compliance values (AC) were significantly lower than those in the control group, indicating that the CCA in acute aortic dissection patients was more rigid.…”
Section: Echo Tracking (Et) Techniquementioning
confidence: 99%